Fenomena Climate Change: Perlindungan Hukum Bagi Pengungsi Iklim di Karibia - Gunawan, Imam (Fakultas Hukum Universitas Primagraha, 2024)
The current phenomenon of climate change is a significant global issue, particularly affecting coastal regions like the Caribbean. The impacts of climate change disrupt stability across various sectors of human life. Consequently, many individuals are compelled to flee their home countries, leading to the emergence of term used to describe those who relocate due to climate-related challenges in their homeland. The purpose of this study is to assess the legal protections available for climate refugees, with a specific focus on the Caribbean, in light of global climate change and the challenges faced both currently and in the future. The research employs a normative legal methodology, which seeks to identify legal rules, doctrines, and principles to address the legal issues at hand, ultimately generating new arguments, theories, or legal concepts in response to these challenges. This research approach incorporates both a legislative and a conceptual framework. The legal materials utilized in this study include primary legal sources, secondary legal sources, and non-legal materials, gathered through literature review techniques. The findings and conclusions of this study aim to advocate for legal protections for climate refugees in the Caribbean, despite the absence of a clearly defined convention governing this issue. The efforts to provide legal protection can be categorized into three aspects: first, human rights; second, the role of states or international organizations; and third, international regulations.